Iraq's hydrocarbon crisis demands integrated remediation solutions: Krisis hidrokarbon Irak menuntut solusi remediasi terpadu - Nour Allah Mahdi Jabbar (Universitas Muhammadiyah Sidoarjo, 2024)
Petroleum hydrocarbon contamination in Iraq’s oil-bearing areas significantly impacts the environment and public health. This study reviews contamination sources, such as oil spills and industrial disposal, and outlines the identification and quantification methods using GC-MS and FTIR. Various remediation strategies, including bioremediation, phytoremediation, chemical oxidation, thermal remediation, and physical removal, are discussed. The review highlights challenges in implementation due to technological, financial, regulatory, and community engagement issues. An integrated adaptive management approach is recommended to mitigate risks and ensure sustainable development of Iraq’s oil sector. Highlight: Hydrocarbon identification and quantification using GC-MS and FTIR. Combined remediation: bioremediation, phytoremediation, chemical oxidation, thermal remediation, physical removal. Challenges: technological, financial, regulatory, and community engagement issues. Keyword: Petroleum hydrocarbon contamination, Iraq, GC-MS, FTIR, remediation strategies